Feeding Management of Sheep for Maximizing Growth, Reproduction and Production - Chaturvedi, O. H.; Shinde, A. K. (Indian Farming, 2015)
Sheep in the country are maintained on extensive grazing system in most of the organized as well as in the traditional farmer’s flocks. Sheep are able to utilize the various grasses, legumes, weeds, herb and browse that grow on millions of acres of cultivated and uncultivated fallow lands, wastelands, forests and native rangelands under extensive range management system for their fodder requirement. This characteristic has made sheep rearing a popular livestock husbandry amongst the poor farmers and landless labourers. Stall feeding of sheep is not common thus more emphasis is given on grazing with supplementation for achieving desirable production. The requirement of sheep on grazing alone is not met, some kind of supplementation either in form of concentrate grain, tree leaves or legume straws is required to enhance mutton and wool production especially during long dry period in tropics. The feeding schedule has been developed for supplementary feeding of sheep on grazing system. Adoption of the feeding schedule improves the overall productivity and reduces losses incurred due to morbidity and mortality.